Childcare in Lampung Saibatin Indigenous Community from the Perspective of Mubadalah and its Contribution to the Development of Family Law in Indonesia - Sutendy, Deddy; Isa, Rozana (SMART: Journal of Sharia, Traditon, and Modernity, 2023)
This article examines childcare in the Lampung Saibatin indigenous community from the perspective of mubadalah and its contribution to the development of family law in Indonesia. This research is field research or filed research conducted in the Lampung Saibatin indigenous community in Lampung Province, conducting interviews with Lampung Saibatin traditional leaders and Lampung Saibatin indigenous people, analyzed qualitatively using the theory of mubadalah. The results of the study show that the Lampung Saibatin indigenous community has a pattern of childcare carried out by the mother, but as time goes by there are already some parents who have implemented that in childcare is carried out jointly by both parents. The existence of care that is dominated by the mother because the father earns a living for the needs of the family, on the other hand there is a classic paradigm that the wife's job is to take care of the house and children while the husband works. In this digital era, it is expected that childcare is carried out jointly, father and mother proportionally, so that this research contributes to campaigning for balanced parenting or mubadalah between father and mother. At the same time as an effort to educate the Lampung Saibatin community who still have a classic paradigm that emphasizes the dominance of childcare only to the mother, so that they can slowly change the paradigm into childcare that has a more balanced value of mubadalah between the father and mother.Keyword: Childcare; Lampung Saibaitin; Mubadalah